Biosurfactant rhamnolipid affacts the desorption of sorbed As(III), As(V), Cr(VI), Cd(II) and Pb(II) on iron (oxyhydr)oxides and clay minerals. (September 2020) - Yang, Ruijie; Wang, Haibing; Shi, Meimei; Jiang, Yongguang; Dong, Yiran; Shi, Liang
Abstract: Rhamnolipids, iron (oxyhydr)oxides and clay minerals are promising agents for mitigating metal and metalloid pollution in the environment. In this study, the adsorption of As(III), As(V), Cr(VI), Cd(II) and Pb(II) on ferrihydrite, goethite, montmorillonite and nontronite, and the impacts of rhamnolipids on their desorption were systematically investigated. As(III), As(V) and Cr(VI) were adsorbed on ferrihydrite and goethite with better adsorptions at lower pH, and their maximum adsorptions ranged from 58.8% to 90.7%. Increased pH enhanced the Cd(II) adsorption on all the tested minerals and the maximum adsorption was 96.6% on montmorillonite at pH 8.0. Pb(II) was completely adsorbed on goethite, montmorillonite and nontronite. Rhamnolipids desorbed Cd(II) and Pb(II) from the minerals, but had no impact on the adsorbed As(III), As(V) and Cr(VI). The maximum desorption of Cd(II) and Pb(II) was 79.6% and 54.0% respectively. Most of the adsorption and desorption kinetics were described well by the pseudo-second order model but the Cd(II) desorption from iron (oxyhydr)oxides was fitted better by the simple Elovich model. These results indicate that the adsorptions of metals and metalloids are both mineral- and pH-dependent. Moreover, rhamnolipids are applicable for enhancing the release of cationic metals associated with minerals in the bioremediation process via washing. Graphical abstract: Image 1 Highlights: Adsorption of metals and metalloids on minerals are selective and pH-dependent. Rhamnolipids have no impact on the desorption of As(III), As(V) and Cr(VI). Cd(II) and Pb(II) could be desorbed from four minerals by rhamnolipids. Pseudo-second order model fits most of the adsorption and desorption kinetics.